Development Of Excel-Based (Nawasena) Basic Financial Accounting Learning Media To Improve Learning Outcomes In The Accounting Cycle - Indah Eka Fitriana; Sukirno Sukirno (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The problem in this study is the low student learning outcomes on financial accounting cycle material. The type of research was research and development with the ADDIE model. With an experimental trial design using a pre-test - post-test control group design model. The feasibility of the product was tested by media experts, learning practitioners, namely teachers, and media users, namely students. The media was tested on the research subjects, namely students of class X AKL 2 SMK Muhammadiyah Dukun. The data collection instruments used were interview guidelines, expert validation questionnaires, teacher response questionnaires, student response questionnaires, and financial transaction questions. The results of the study show: (1) Basic Financial Accounting Learning Media Product